ANALYSIS OF REGIONAL ASSET CONTROL IN INCREASING THE OPTIMIZATION OF REGIONAL ASSET MANAGEMENT - Noratni, Rita (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Assets are a component that, with correct management, can yield data that can be accounted for in a region’s financial reports. One of the cornerstones to effective regional economic development is regional asset management. If regional assets are effectively handled, public confidence in the administration of state finances will rise. The goal of the asset management process’s strategy for improving regional asset management is to maximize the utilization of regional assets through asset inventory, legal audits, asset supervision and control, and asset handover. To determine the many factors that affect the optimization of regional assets, a literature review study was carried out. Asset inventory, legal audit, supervision and control of assets, as well as the transfer of assets, are the factors that have the most impact on the optimization of regional assets. The dependent variable is asset management optimization, while the independent variables are asset inventory, legal audit, asset monitoring and control, and asset value. The findings of the literature research demonstrate a beneficial relationship between asset inventory, legal audit, asset monitoring and control, and asset valuation and regional asset management optimization.